2020
DOI: 10.1158/1535-7163.mct-19-0929
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels and Their Role in the Pathophysiology of Gliomas

Abstract: Malignant gliomas are the most common primary central nervous system tumors and their prognosis is very poor. In recent years, ion channels have been demonstrated to play important roles in tumor pathophysiology such as regulation of gene expression, cell migration, and cell proliferation. In this review, we summarize the current knowledge on the role of ion channels on the development and progression of gliomas. Cell volume changes through the regulation of ion flux, accompanied by water flux, are essential f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 97 publications
1
15
0
Order By: Relevance
“…Many of the top differential genes have been reported to be linked to glioblastomia, including PRRX1 22 , MRC2 23 , LAMC1 24 , BNIP3 25 , VEGFA 26 , SLC2A1 27 , and NTRK2 28 . Many enriched GO terms associated with the differential genes (Figure 2f) are reported in previous literature, including blood vessel development 29 , chemical synaptic transmission 30 , and ion channels 31 . Utilizing the gene expression data from The Cancer Genome Atlas (TCGA 32 , Methods), we found that the spatially differential genes identified by Paella have the highest overlap with highly variable genes across GBM and low-grade glioma (LGG) samples from TCGA, followed by samples of other cancers types (Figure 2g).…”
Section: Mainsupporting
confidence: 58%
“…Many of the top differential genes have been reported to be linked to glioblastomia, including PRRX1 22 , MRC2 23 , LAMC1 24 , BNIP3 25 , VEGFA 26 , SLC2A1 27 , and NTRK2 28 . Many enriched GO terms associated with the differential genes (Figure 2f) are reported in previous literature, including blood vessel development 29 , chemical synaptic transmission 30 , and ion channels 31 . Utilizing the gene expression data from The Cancer Genome Atlas (TCGA 32 , Methods), we found that the spatially differential genes identified by Paella have the highest overlap with highly variable genes across GBM and low-grade glioma (LGG) samples from TCGA, followed by samples of other cancers types (Figure 2g).…”
Section: Mainsupporting
confidence: 58%
“…Ion channel malfunctions can influence the extracellular concentrations of ions and neurotransmitters, inducing neuronal hyperexcitability that lead to seizures [ 29 ]. Altered ion channels are also associated with the proliferation and invasion of glioma cells [ 30 ]. In this study, functional enrichment analysis revealed that ion channel activities (especially potassium ion channels) were overactivated in patients with GRE.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, ion currents are involved in neuron-glioma crosstalk. Ion channels exist in the CNS, primarily Na + , K + , Ca 2+ and Cl − channels, which regulate cell migration, invasion, proliferation and apoptosis ( 34 ). Specifically, the K + channel members include voltage-gated K + channels (VGKC or Kv), calcium-activated K + channels (KCa) and ATP-sensitive K + channels (KATP).…”
Section: Neuronal Regulation In Glioma Progressionmentioning
confidence: 99%